2019
DOI: 10.15666/aeer/1704_1015510172
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Phytobenthos for the Ecological Status Assessment in Upper Sakarya Basin, Turkey

Abstract: In this study, it was aimed to use diatoms as representatives of phytobenthos for estimating the ecological status in Upper Sakarya Basin. Samples were taken seasonally from ten stations from April 2015 to December 2015. Stations 1, 2, 3, 4, 5, 6 and 7 were selected from rivers, stations 8 and 9 were selected from ponds which form Sakarya Springs. Station 10 was located at the outlet of Cifteler Aquaculture and Research Station. Diatoms were identified, counted and 19 diatom indices were calculated. Moreover, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 12 publications
0
13
1
Order By: Relevance
“…In a study carried out in the Upper Sakarya Basin [29], Achnanthidium minutissimum showed domination, but was not a dominant diatom species in the present study. In earlier classifications this species was considered as indicator of high ecological studies-for IPS index [21] was highly sensitive.…”
Section: Discussioncontrasting
confidence: 65%
See 3 more Smart Citations
“…In a study carried out in the Upper Sakarya Basin [29], Achnanthidium minutissimum showed domination, but was not a dominant diatom species in the present study. In earlier classifications this species was considered as indicator of high ecological studies-for IPS index [21] was highly sensitive.…”
Section: Discussioncontrasting
confidence: 65%
“…This is why, as pointed out recent studies [12,18], this species should be excluded from water quality assessments in Europe. This issue likely explains why the earlier studies [29] show mainly good and/or high quality status in the Sakarya River. Contrary to previous studies, the present study indicates much lower water quality around the same bodies of water.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…To develop metrics or indices for bioassessment, algal species need to be linked to their autecological traits, such as organic pollution tolerance or functional groups, but sources of trait information are not available for many regions. To monitor pollution from agriculture, aquaculture, and recreation in rivers and ponds within the Sakarya Basin in Turkey, Cetin, and Demir (2019) selected the Pampean Diatom Index (PDI) after comparison with 18 other indices calculated using the OMNIDIA software because of higher correlations between the PDI and total N.…”
Section: Algaementioning
confidence: 99%